Fragmented Flying Geese (FFG) and intra-regional agglomeration: Towards a model explaining location shifting of Japanese multinational corporations and the electric value chains of ASEAN economies - Minh Tam T. Bui; Rumi Miura; Masami Saito; Yusuke Shibata; Keiichiro Suenaga (Economies, 2022)
In this article, we study corporate behavior and develop a model for trends and factors in Japanese Multinational Corporations (MNCs) in the electrical and electronic industry that have played an important role in the economic development of East and Southeast Asia. We focus on Thailand, where Japanese MNCs are still increasing, and examine the practical applicability of the model. Basically, the model will be developed based on the existing flying geese model and regional agglomeration, but it will also be developed to explain new events such as progress in the division of labor by fragmentation and intra-regional agglomeration in East and Southeast Asia. Japanese MNCs in the electrical and electronic industry have shifted their production bases to developing countries one after another, as a variant of the third type of flying geese model. While the network of the international division of labor is forming with the development of fragmentation, the area around the eastern seaboard from Bangkok is playing an increasingly important role in the network of Japanese companies. In that sense, this study contributes to the body of literature on flying geese models with a modified model embodied with dynamic and systematic features of the ASEAN integrated economies.
Keywords: F23; F63; L63; O24; O53; 330; electric industry; fragmented flying geese (FFG); intra-regional agglomeration; regional value chains (RVCs)